Mitigation of salt stress in wheat seedlings by halotolerant bacteria isolated from saline habitats - Ramadoss, Dhanushkodi (Springer International Publishing AG, 2013)
Eighty four halotolerant bacterial strains were isolated from the saline habitats and screened for growth at different NaCl concentrations. All grew well at 5% NaCl, but only 25% isolates showed growth at 20% NaCl concentration. Five strains SL3, SL32, SL35, J8W and PU62 growing well in 20% NaCl concentrations were further characterized for multiple plant growth promoting traits such as indole −3- acetic acid (IAA) production, HCN and siderophore production, ACC deaminase activity and P-solubilization. None were positive for HCN production and PCR amplification of acdS, the structural gene for ACC deaminase enzyme was found negative. 16S rRNA gene sequencing analysis of the five strains showed them to belong to two genera Bacillus and Hallobacillus. In vitro experiments showed that salt concentrations had significant inhibitory effects on development of seedlings but not on the growth of the bacterial strains. Inoculation of the 5 halotolerant bacterial strains to ameliorate salt stress (80 mM, 160 mM and 320 mM) in wheat seedlings produced an increase in root length of 71.7% in comparison with uninoculated positive controls. In particular, Hallobacillus sp. SL3 and Bacillus halodenitrificans PU62 showed more than 90% increase in root elongation and 17.4% increase in dry weight when compared to uninoculated wheat seedlings at 320 mM NaCl stress indicating a significant reduction of the deleterious effects of NaCl. These results indicate that halotolerant bacteria isolated from saline environments have potential to enhance plant growth under saline stress through direct or indirect mechanisms and would be most appropriate as bioinoculants under such conditions.